Comparative Efficacy of Two Bentazone + MCPA Herbicide Formulations for Weed Control and Vegetative Growth of Rice (Oryza sativa L.) cv. Inpari 32 - Rizqi Nurul Huda; Mohamad Nasirudin; Abu Na’im (International Journal of Interdisciplinary Research, 2026)
Weed infestation remains one of the major constraints limiting rice productivity because it competes with crops for water, nutrients, light, and growing space. This study aimed to compare the effectiveness of two selective herbicide formulations containing Bentazone (400 g L⁻¹) + MCPA (60 g L⁻¹), commercially marketed as Basagran® and Bentagram®, in suppressing weeds and supporting the vegetative growth of rice (Oryza sativa L.) cv. Inpari 32. The experiment was conducted in irrigated rice fields in Jombang Regency, East Java, Indonesia, from May to June 2025 using a Completely Randomized Design (CRD). Treatments consisted of six herbicide doses (0.5, 0.75, 1.0, 1.25, 1.5, and 1.75 L ha⁻¹) and an untreated control, each replicated twice. Data on weed diversity, dominance index, weed dry weight, plant height, and tiller number were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test at the 5% significance level. The application of both herbicides reduced weed diversity, with the Shannon–Wiener diversity index ranging from 1.39 to 1.56 and Simpson's dominance index remaining low (0.22–0.25), indicating effective weed suppression without dominance of any weed species. Basagran had no significant effect (p > 0.05) on plant height, tiller number, or weed dry weight, whereas Bentagram significantly increased tiller number (p < 0.05) while maintaining normal plant growth. Although the highest numerical responses were occasionally observed at 1.75 L ha⁻¹, they were not significantly different from those at 1.5 L ha⁻¹. Therefore, 1.5 L ha⁻¹ was identified as the optimum application rate because it effectively suppressed weeds without causing phytotoxicity or adversely affecting rice vegetative growth. These findings demonstrate that Bentazone + MCPA herbicides can be effectively incorporated into sustainable weed management programs to improve rice cultivation efficiency while minimizing unnecessary herbicide inputs.